Polycyclic aromatic hydrocarbons (PAHs) in fine fractions of Barapukuria coal in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2019)
The existence and distribution of polycyclic aromatic hydrocarbons (PAHs) in fine coal fractions have been determined in order to evaluate their potential carcinogenicity to human beings. Thirteen PAHs of fine coal fractions (n = 9) from Barapukuria coal field, situated at the northwestern part of Bangladesh were analyzed by the gas chromatography-mass spectrometry (GC−MS) method in order to examine their distributions and toxicity in the environment. Relative abundances of fluoranthene (Flu), pyrene (Pyr), benzo [b,j,k] fluoranthene (Bflas), benzo [e] pyrene (BeP) and benzo [a] pyrene (BaP) were found to be high, followed by phenanthrene (Phe), indeno [1,2,3-cd] pyrene (InP), benzo [g,h,i] perylene (BghiP) and coronene (Cor). The average loads of carcinogenic PAHs in the fine coal fractions decreased in the order: Bflas > BeP > BaP > BghiP > InP > Cor. The PAHs ratios of BeP/(BeP + BaP) ranging from 0.61 to 0.85 (average 0.74), reflected the decay of BaP due to ageing in prolonged exposure to the solar radiation. High abundance of land plant markers retene (Ret) and Phe and BaP/BghiP ratio (~0.10 to 6.16, average 1.89) values indicate that organic matters in the studied samples were derived from typical biological sources. Moreover, the existence of more middle- and higher molecular weight (MMW and HMW) PAHs over lower molecular weight (LMW) PAHs in most samples implied the association of high toxicity with negative impacts on human health. The health risk assessment factors (BaPeq) ranging from 0.55 ng g–1 to 6.51 ng g–1 indicates moderate to high health risk related to carcinogenic PAHs in the surrounding atmosphere. The estimated incremental lifetime cancer risk (ILCR) values for adults (9.96 × 10−5 to 1.27 × 10−4) and children (5.56 × 10−6 to 1.12 × 10−6) were found to be higher than or equal to the range of 1.0 × 10−6 to 1.0 × 10−4.Bangladesh J. Sci. Ind. Res.54(3), 203-214, 2019